Susceptibilities of pus cultures in diabetic foot patients: an observational study. Issue 3 (8th July 2022) - Asghar, Muhammad Sohaib; Parkash, Om; Sagar,; Singh, Manjeet; Kumar, Sumeet; Kumar, Karan; Mehdi, Asad; Khan, Farmanullah; Chughtai, Najeebullah; Ahmed, Nisar
Abstract : Objectives: The aim of our study is to evaluate the organisms growing into the pus cultures of diabetic foot patients and to further document their sensitivity and resistance toward antibiotics. Methods: This study was conducted among admitted patients in the department of Medicine and Orthopedics, of a tertiary care hospital, including patients with known diabetes mellitus for the last 5 years, with a foot ulcer of any grade and a positive culture for bacterial growth. Cultures showing fungal growth were excluded. Results: There were 139 participants in our study with a mean age of 55.27 years, and mean HbA1c levels of 9.51%, 101 (72.66%) patients were males and 38 (27.33%) females. According to the Wagner classification; there were 48 (34.53%) patients in grade 2, 27 (19.42%) patients in grade 3, 54 (38.84%) patients in grade 4, and 10 (7.19%) patients in grade 5. The most frequently isolated bacteria were Staphylococcus aureus (43.16%), methicillin-resistant staphylococcal aureus (5.03%), Enterococcus species (5.75%), Streptococcus species (7.91%), Pseudomonas aeruginosa (20.14%), Escherichia coli (24.46%), Klebsiella pneumonia 7 (5.03%), Proteus vulgaris 6 (4.31%), Proteus mirabilis 3 (2.15%), Enterobacter species 7 (5.03%), Morganella morganii 2 (1.43%), and Acinetobacter 7 (5.03%). Amikacin was the most susceptible antibiotic to the majority of the microorganisms, followed by gentamicin, piperacillin/tazobactam, vancomycin chloramphenicol, and clindamycin. Among the resistant antibiotics, penicillins and cephalosporins were the notable ones. Conclusions: This study will decipher the bacteriological profiles among patients of diabetic foot ulcers according to their susceptibility and might be helpful to provide effective treatment.